음악요법이 노인의 우울과 삶의 만족도에 미치는 영향 - 박미정(Mi Jeong Park); 정영(Young Chung) (지역사회간호학회지, 2005)
Purpose: This research was carried out to examine if music therapy is effective in decreasing elderly people's depression level and in increasing their life satisfaction level Methods: This study used the quasi-experimental design with nonequivalent control group and the pre-test and post-test design, and was conducted from the 26th of July to the 26th of September in 2004. Data were collected using a questionnaire developed by Y.esavage et al. (1983) to measure depression level and one developed by Yoon (1982) to measure life satisfaction level. The subjects were 80 elderly people who were the members of an elderly welfare center in G city. The subjects were divided into an experimental group (n=40) and a control group (n=40). Results: The first hypothesis 'The depression level will be lowered in the experimental group who received music therapy' was supported (t=3.856, p=.000). The second hypothesis 'The life satisfaction level will be raised in the experimental group who received music therapy' was supported (t=2.040, p=.045). The results above suggest that music therapy can be an effective nursing intervention for reducing the depression level and increasing the life satisfaction level of elderly people.